Association between on-road driving performance test and usual walking speed or sustainable attention in the elderly; Preliminary survey. (2nd January 2022) - Tanaka, Yuta; Kume, Yu; Kodama, Ayuto
Abstract: Objective: An increase in older drivers has been widely recognized in Japan; accordingly, screening to prevent traffic accidents is a crucial issue for safe driving. As a preliminary study, we examined the association between on-road driving performance and cognition or physical performance in older individuals. Methods: The survey was conducted in 2020, and the participants were recruited in Katagami City, Akita, Japan. The Road Test was used to assess on-road driving performance. The physical assessment comprised the usual walking speed (UWS) and grip strength (GS), and the cognitive evaluation consisted of the National Center for Geriatrics and Gerontology Functional Assessment Tool (NCGG-FAT) and the Japanese version of Stroke Drivers' Screening Assessment (J-SDSA). A multiple regression model was also applied to examine the association between on-road driving performance and the physical items or cognitive domains of the NCGG-FAT and the J-SDSA in older individuals. Results: Twenty-one participants (mean age ± standard deviation [SD], 77.0 ± 5.5 years) were included in this study. A correlation analysis showed that the on-road test score was correlated with performances on the UWS ( r = 0.53, p = .002), the word list memory (WM) test ( r = 0.44, p = .046), the trail-making test-A (TMT-A) ( r = −0.44, p = .048), the SDSA dot cancelation (DC) test ( r = −0.63, p = .002), and the SDSA squares matrix compass test (SM) ( r = 0.54, p = .048). According to a stepwise linear regression, the on-road test score was associated with the UWS ( β = −0.01, p = .003) and the SDSA DC ( β = 4.89, p = .01), with an adjusted R 2 = 0.54. Conclusions: The results of the study suggested that the UWS and sustainable attention might be potential factors influencing on-road driving performance. Our preliminary findings warrant further investigation.